The Implementation of Trauma Healing to The Bullying at Rumah Duta Revolusi Mental Semarang - Kibtyah, Maryatul; Rohmah , Ana Mawadda; Maulana, Khabib Akbar (Proceedings of International Conference on Da'wa and Communication, 2021)
This research describes the implementation of trauma healing to victims of bullying at the Rumah Duta Revolusi Mental in Semarang City using Islamic Counseling Guidance. The collecting data technique were interviews, observation, and documentation. Furthermore, the data analysis technique used the Milles and Huberman model, namely: data reduction, data presentation, and data verification. The results showed that the implementation of trauma healing to victims of bullying at the Rumah Duta Revolusi Mental in Semarang City had two forms of programs, namely counseling and psychotherapy including several therapies, namely play therapy, emotional catharsis, fairy tale therapy, and, writing therapy. Meanwhile, trauma healing is carried out through three stages, namely the initial stage, the middle stage or the work stage, and the final stage or the termination stage. Judging the Islamic Counseling Guidance, both in terms of the objectives, functions, and methods of trauma healing to the victims was an implementation of the techniques, stages, methods of trauma healing.